IMPLEMENTATION OF GENDER MAINSTREAMING IN REALIZING SUSTAINABLE DEVELOPMENT OBJECTIVES IN PEKANBARU - Azilah Maysarah Siregar; Irdayanti Irdayanti; Mustiqowati Ummul Fithriyyah (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2023)
The presence of an increase in cases of violence against women in the household, accompanied by services for women and victims of violence that are not optimally available, and the limited empowerment of women victims in Pekanbaru City are some of the phenomena that underlie this research. This study used qualitative research to describe the implementation of gender mainstreaming in Pekanbaru to realize one of the sustainable development goals (SDGs) in gender equality, with one of the targets of eliminating sexual violence in public and private spaces. There are two techniques for determining research informants, namely purposive sampling and then followed by snowball sampling. Then the data analysis technique used in this research is a qualitative descriptive analysis technique, which describes specific things with data obtained through observation, interviews, and documentation. The results of the study state that the implementation of gender mainstreaming as an effort to realize the SDGs goals has not been optimally implemented, with indicators stating that the problem of achieving gender equality through the elimination of sexual violence in public and private spaces is difficult to control, the ability of policies to structure the implementation process clear and detailed and the presence of various factors outside the policy variables that affect the implementation process.